Beneficial effects of multisensory and cognitive stimulation on age-related cognitive decline in long-term-care institutions - Oliveira TCG (Dove Medical Press, 2014)
Thaís Cristina Galdino De Oliveira,1 Fernanda Cabral Soares,1 Liliane Dias E Dias De Macedo,1 Domingos Luiz Wanderley Picanço Diniz,1 Natáli Valim Oliver Bento-Torres,1,2 Cristovam Wanderley Picanço-Diniz1 1Laboratory of Investigations in Neurodgeneration and Infection, Biological Sciences Institute, University Hospital João de Barros Barreto, 2College of Physical Therapy and Occupational Therapy, Federal University of Pará, Belém, Brazil Abstract: The aim of the present report was to evaluate the effectiveness and impact of multisensory and cognitive stimulation on improving cognition in elderly persons living in long-term-care institutions (institutionalized [I]) or in communities with their families (noninstitutionalized [NI]). We compared neuropsychological performance using language and Mini-Mental State Examination (MMSE) test scores before and after 24 and 48 stimulation sessions. The two groups were matched by age and years of schooling. Small groups of ten or fewer volunteers underwent the stimulation program, twice a week, over 6 months (48 sessions in total). Sessions were based on language and memory exercises, as well as visual, olfactory, auditory, and ludic stimulation, including music, singing, and dance. Both groups were assessed at the beginning (before stimulation), in the middle (after 24 sessions), and at the end (after 48 sessions) of the stimulation program. Although the NI group showed higher performance in all tasks in all time windows compared with I subjects, both groups improved their performance after stimulation. In addition, the improvement was significantly higher in the I group than the NI group. Language tests seem to be more efficient than the MMSE to detect early changes in cognitive status. The results suggest the impoverished environment of long-term-care institutions may contribute to lower cognitive scores before stimulation and the higher improvement rate of this group after stimulation. In conclusion, language tests should be routinely adopted in the neuropsychological assessment of elderly subjects, and long-term-care institutions need to include regular sensorimotor, social, and cognitive stimulation as a public health policy for elderly persons. Keywords: aging, multisensory stimulation, cognition, language, impoverished environment, long-term-care institutions